Rare paraneoplastic syndromes in digestive systems caused by lung cancer. Issue 2 (5th February 2021) - Kamimura, Hiroteru; Iwasaki, Tomohiro; Hayashi, Kazunao; Terai, Shuji
Abstract : We observed a rare case of two different digestive paraneoplastic syndromes that improved with the treatment of the neoplasms. The first syndrome was chronic intestinal pseudo-obstruction (CIPO), which is a subtype of paraneoplastic syndromes called a paraneoplastic neurological syndrome (PNS). The second was Stauffer's syndrome, which is a unique paraneoplastic syndrome characterised by non-metastatic intrahepatic cholestasis associated with neoplasms. Here, we report the case of a 55-year-old man who presented with two concurrent paraneoplastic syndromes in the digestive system. The intestinal pseudo-obstruction and elevated biliary enzyme levels improved as the lung cancer responded to chemotherapy. In this case, CIPO as a PNS led to the detection of lung cancer. To our knowledge, this is the first report of Stauffer's syndrome caused by lung adenocarcinoma.